2019
DOI: 10.1021/acsami.9b04261
|View full text |Cite
|
Sign up to set email alerts
|

GO-Functionalized Large Magnetic Iron Oxide Nanoparticles with Enhanced Colloidal Stability and Hyperthermia Performance

Abstract: Because of their high magnetization and suitable biocompatibility, iron-oxide nanoparticles (IONPs) have been widely employed in various biomedical applications, including magnetic hyperthermia for cancer treatment. In many cases, the colloidal stability requirement will limit the usage of ferromagnetic particles that are usually associated with good magnetic response. To address this challenge, a stable carrier for better colloidal stability regardless of the size or shape of the IONPs while at the same time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…These unique characteristics provide special sites for immobilization and functionalization by various moieties including polymeric materials such as polyethylenimine [10], chitosan [11], poly(lactic acid) [12,13], and inorganic nanostructures including gold [14], TiO 2 [15], silver nanoparticles [16] and iron oxide nanoparticles [8,14]. Specifically, iron oxide nanoparticles exhibited magnetic characteristics that could be applied to various applications, especially for magnetic fluid hyperthermia [17], magnetic-based bio-separation [18], diagnosis and treatment of infections of bacteria [19], and inductive heating-based magnetic field exposure [20]. Currently, the combination of graphene-based materials and iron oxide nanoparticles have attracted attention due to their potential characteristics as graphene-based materials combined with magnetic nanoparticles [21].…”
mentioning
confidence: 99%
“…These unique characteristics provide special sites for immobilization and functionalization by various moieties including polymeric materials such as polyethylenimine [10], chitosan [11], poly(lactic acid) [12,13], and inorganic nanostructures including gold [14], TiO 2 [15], silver nanoparticles [16] and iron oxide nanoparticles [8,14]. Specifically, iron oxide nanoparticles exhibited magnetic characteristics that could be applied to various applications, especially for magnetic fluid hyperthermia [17], magnetic-based bio-separation [18], diagnosis and treatment of infections of bacteria [19], and inductive heating-based magnetic field exposure [20]. Currently, the combination of graphene-based materials and iron oxide nanoparticles have attracted attention due to their potential characteristics as graphene-based materials combined with magnetic nanoparticles [21].…”
mentioning
confidence: 99%
“…Relatively few papers [55][56][57] were published on the possible application of graphene oxide/magnetite nanocomposites for magnetic hyperthermia, and only one was found related to the study of the heat production of reduced GO/MNP in an AC magnetic field [58]. Rodrigues et al reported on interesting multifunctional graphene-based magnetic nanocarriers for combined hyperthermia and drug delivery [55].…”
Section: Perspectives On Magnetic Hyperthermia Of Rgo/mnp Compositesmentioning
confidence: 99%
“…Albeit reduced GO/MNP was discussed throughout the paper, none of the broad classes of reducing agents were directly applied, only the possible decomposition (resulting in a loss of oxygen content, which is often misinterpreted as a true chemical reduction) of GO during the co-precipitation of magnetic nanoparticles was assumed. A solvent evaporation method was applied by Sugumaran et al to reside iron oxide nanoparticles of various core sizes in the GO sheet based host [57]. The PEGylated GO/MNP composites with the largest MNP core size showed not only outstanding hyperthermic efficiency with SAR value higher than 5000 W/g, but they exhibited excellent colloid stability as well.…”
Section: Perspectives On Magnetic Hyperthermia Of Rgo/mnp Compositesmentioning
confidence: 99%
“…26 Optimization of hyperthermia treatments clearly requires, as a necessary condition, optimization of the mechanism of heat release from magnetic NPs, in order to maximize their specic loss power (SLP), 6,[27][28][29] dened as the total power released by the magnetic nanoparticles divided by their total mass. This can be done by either looking for higher-performance magnetic nanomaterials 30,31 and better particle sizes and shapes, 32,33 or trying to devise methods to more efficiently extract the heating power from a given system of nanoparticles. 28 In most in vitro and in vivo applications, the particles are activated by using a radio-frequency (RF) harmonic magnetic eld.…”
Section: Introductionmentioning
confidence: 99%